KATP channels and insulin secretion - Ashcroft, Frances Mary (Henry Stewart Talks, 2012)
KATP channels and insulin secretion, Structure of the KATP channel, Functional roles, Regulation by metabolism, nucleotides and lipids, Overview of insulin secretion and diabetes, Effects of loss-of-function KATP channel mutations, Effects of gain-of-function KATP channel mutations, Implications for the treatment of neonatal diabetes